(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Since none can deny the actual fact that the influence of natural language always remains visible on other acquired languages (whether second or foreign). This can be so because, aside from some exceptions, none can express his thought, emotion, ideas etc. as effectively and clearly in other language as he can express through his first language. The touch of maternal language always persists. It’s altogether impossible to stay the work and speech of other language, off from the impact of natural language. This particular tendency may be all right observed in English Language when it’s utilized by a person apart from British people. Due to this unique tendency English has grown into various varieties, even within the countries where it’s used as maternal language or native language thus, the method of globalization occurred. English, a cosmopolitan means of communication, is now being studied and utilized by variety of well-trained investigators on either side of Atlantic. These investigators and students, knowingly or unknowingly, contribute to complement the language. In the present research work, entitled “Indianization of English A Descriptive Study of Indian English” efforts are made to determine Indian English as one of the powerful variety. The work ascertains that none other kind of English can perform the unique and particular functions as Indian English often accomplishes, not only at local or national level but also at world level. Contribution of Indian English in the structural growth and development of the language can’t be ignored. Thus, an in depth study on Indian English is presented in the present research work.